O ACENTO EM COMBINAÇÕES COM PARTÍCULAS ENCLÍTICAS EM LATIM - Quednau, Laura Rosane (Organon, 2012)
This paper presents a study about enclitic stress in Latin. According to the testimonies of anumber of Roman grammarians, enclitics like the monosyllabic conjunction -que uniformly induce stresson the immediately preceding syllable, i.e., the final syllable of the host word, irrespective of syllablequantity. However, we will show that the weight of the immediately preceding syllable plays a crucialrole in enclitic stress: if this syllable is heavy, the stress falls on it; if it is light, the stress falls on the sameposition it would fall in the host word without the enclitic.